Galectin-13 and Laeverin Levels Interfere with Human Fetoplacental Growth - Vincze Márió Attila (INTERNATIONAL JOURNAL OF MOLECULAR SCIENCES, 2024)
Galectin-13 (Gal-13) is predominantly produced by the syncytiotrophoblast, while laeverin is expressed on the outgrowing extravillous trophoblast, and both are thought to be biomarkers of preeclampsia. The aim of this study was to assess the correlation between concentrations of Gal-13 and laeverin measured in maternal serum and amniotic fluid at 16–22 weeks of gestation and the sonographic assessment of the fetoplacental measurements. Fetal biometric data and placental volume and perfusion indices were measured in 62 singleton pregnancies. Serum and amniotic levels of Gal-13 and laeverin levels were measured using a sandwich ELISA. Both amniotic fluid and serum Gal-13 levels expressed a negative correlation to the plasma laeverin level in mid-pregnancy. Serum laeverin level correlated positively with the gestational length at delivery (β = 0.39, p < 0.05), while the amniotic laeverin level correlated well with the abdominal circumference of the fetus (β = 0.44, p < 0.05). Furthermore, laeverin level in the amnion correlated positively with the estimated fetal weight (β = 0.48, p < 0.05) and with the placental volume (β = 0.32, p < 0.05). Logistic regression analyses revealed that a higher circulating Gal-13 level represents a slightly significant risk factor (OR: 1.01) for hypertension-related diseases during pregnancy. It is a novelty that laeverin can be detected in the amniotic fluid, and amnion laeverin concentration represents a potential biomarker of fetoplacental growth.